2021
DOI: 10.3390/app11010395
|View full text |Cite
|
Sign up to set email alerts
|

Role of Autologous Platelet Gel (APG) in Bone Healing: A Rabbit Study

Abstract: Purpose: The aim of the present study is to evaluate the influence and efficacy of autologous platelets on bone regeneration in a rabbit defects model. Materials and Methods: A total of 12 critical size tibial defects were produced in six New Zealand rabbits: A total of six defects were filled with autologous platelet gel (APG) and six defects were maintained as untreated controls. No membranes were used to cover the bone osteotomies. The histology and histomorphometry were performed at four weeks on retrieved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Different studies have reported that the APG clots form a dense fibrin structure, with many ramifications and little spacing observed, especially where platelets are activated [ 53 , 54 ]. A justification of this could be that highly procoagulant cells, for example activated platelets, produce a contractile force among the adjacent filaments, tightening them between the anchoring points of the network [ 27 ]. The structural proteins and fibrin network can be scaffolded and can be influenced by the osteoprogenitor cells migrating towards the bone defect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different studies have reported that the APG clots form a dense fibrin structure, with many ramifications and little spacing observed, especially where platelets are activated [ 53 , 54 ]. A justification of this could be that highly procoagulant cells, for example activated platelets, produce a contractile force among the adjacent filaments, tightening them between the anchoring points of the network [ 27 ]. The structural proteins and fibrin network can be scaffolded and can be influenced by the osteoprogenitor cells migrating towards the bone defect.…”
Section: Discussionmentioning
confidence: 99%
“…PC were originally introduced by Marx et al [ 20 ], Anitua [ 21 ], and Choukroun [ 22 ] in the early 1990s and their applications are increasing in many medical fields, such as esthetic medicine [ 23 ], orthopedics [ 24 ], wound repair, military drill [ 25 ], ophthalmology [ 26 ] and, of course, in dentistry. PC have been proposed for soft and hard tissue surgery in many different forms as clots reduce in thick membranes to improve the healing of the damaged tissues and the mechanical/ biological behavior of biomaterials and scaffolds [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The motion was assessed using digital model superposition at T0, T1 (30 days), and T3 (60 days). Movement occurred 35% more on the PRP than on the C Side, altering the OPG and sRANKL levels in GCF [27,83].…”
Section: Prp and Prfmentioning
confidence: 96%
“…The information and data obtained are all in agreement in confirming the immuno-modulating and regenerative properties of SCs with evident improvements in anti-inflammatory, osteogenic and angiogenic activity. Part of this effect is surely due to the intrinsic ability of stem cells to secrete anti-inflammatory and angiogenic cytokines and growth factors, such as IL-10 and TGF-beta [ 297 , 298 , 299 , 300 ]. Peripheral blood has shown some advantages over other solutions for everything related to the use of PB-SCs for clinical purposes in vivo.…”
Section: Stem Cells Therapies For Regenerative and Translational Medi...mentioning
confidence: 99%